Polykystose rénale et leucémie myéloïde chronique : association rare - VIGAN, J; AGBOTON, Bruno Leopold; AHOUI, S; ANANI, L; LATOUNDJI, S (My University, 2014)
Cas clinique
Keywords: Polycystic kidney didease; chronique myeloid leukemia; calculi cysts; imatnib; Benin